The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.46827/ejsss.v6i2.998
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Influencing Drug Abuse Among Youths in Informal Settlements: A Case Study of Mathare Slums, Nairobi County, Kenya

Abstract: Large population of youths in informal settlement in Kenya are involved in a number of social vices. These vices may include but not limited to robbery with violence, early marriages, dropping out of school and joining outlawed gangs. Youth involvement in social vices presents great concern to parents, government and non-governmental organizations. With increased prevalence of social vices in informal settlements in Kenya, this study was motivated to investigate the influence of psychosocial factors on drug ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Anulo (2017); Friesen et al (2018); Ochocho et al (2018);and Zweig (2016) in their studies, argued that demographic indicators, such as age and marital status have contributed for the expansion of informal settlements. Also Heshmati and Zarabadi (2016); Meshkini et al (2015); and Mwacharo (2012) demonstrated that family size has a significant effect on the expansion of informal settlements. Large family size has its own contributions for the people who choose to live in informal settlements.…”
Section: Demographic Factorsmentioning
confidence: 98%
See 2 more Smart Citations
“…Anulo (2017); Friesen et al (2018); Ochocho et al (2018);and Zweig (2016) in their studies, argued that demographic indicators, such as age and marital status have contributed for the expansion of informal settlements. Also Heshmati and Zarabadi (2016); Meshkini et al (2015); and Mwacharo (2012) demonstrated that family size has a significant effect on the expansion of informal settlements. Large family size has its own contributions for the people who choose to live in informal settlements.…”
Section: Demographic Factorsmentioning
confidence: 98%
“…Accordingly, through exploring previous empirical studies, seventeen variables from demographic, socio-economic, administrative, and political and legislative dimensions, such as age, marital status, family size, educational level, inconsistency of plan and land legislations, corruption, rigid building regulation of legal houses, procedural problems of legal land provision, inefficient public administration, inadequate housing policy, high land price in the formal land market, land speculation, high housing rent, income disparity, population growth, land substitution modality, and political situation have considered and contextualized in this study (see Table 1). In the previous studies, these factors have been identified and justified using descriptive statistics (Akirso, 2021;Ali & Sulaiman, 2006;Anulo, 2017;Asefa, 2020;Baye, Wegayehu, & Mulugeta, 2020;Dadi, 2018;G/Silassie, 2019;Hadush, 2019;Matamanda, 2019;Mensah et al, 2013;Msuya et al, 2017;Mwacharo, 2012;Sakala, 2016;Wondimu, 2021), binary logistic regression model (Ochocho et al, 2018;Minetos & Polyzos, 2013), and factors analysis or principal component analysis methods (Heshmati & Zarabadi, 2016;Meshkini et al, 2015).…”
Section: Determinant Factors For the Expansion Of Informal Settlementsmentioning
confidence: 99%
See 1 more Smart Citation